Dimethylfumarate: potency prediction and clinical experience. (16th April 2013) - Basketter, David A.; White, Ian R.; Burleson, Florence G.; Burleson, Gary R.; Kimber, Ian
<x xml:space="preserve">Abstract</x> Background. Dimethylfumarate (DMF) was the cause of a major outbreak of allergic contact dermatitis as a consequence of its use as an antifungal agent in leather products, particularly in furniture, with what became known as 'toxic sofa dermatitis'. Objectives. To determine whether the frequency and severity of reactions to DMF arose as a function of its intrinsic potency and/or the nature and extent of exposure. Methods. The intrinsic potency of DMF was measured with the standard local lymph node assay (LLNA), with determination of an EC3 value, which is the threshold in the LLNA and serves as an indicator of relative skin‐sensitizing potency in humans. Results. The EC3 value for DMF was 0.35% when tested in dimethylformamide as a vehicle, indicating that DMF is a strong, but not an extreme, skin sensitizer in this mouse model. Conclusions. DMF appears to have a sensitizing potency in the mouse that is very similar to that of formaldehyde, which is also a strong human skin sensitizer. However, the frequency and intensity of allergic contact dermatitis reactions to DMF suggest that it was the prolonged, repeated and occlusive exposure to this chemical over large skin areas, combined with the strong sensitizing potency, that generated the 'perfect storm' conditions that caused the DMF epidemic.